Virtual workshops to preserve interprofessional collaboration when physical distancing. Issue 7 (2nd June 2020) - Kent, Fiona; George, Johnson; Lindley, Jennifer; Brock, Tina
Abstract : With this issue we begin print publishing the responses received in our call for Medical Education Adaptations: Lessons learned from educators' experiences rapidly transforming practice on account of COVID‐19 related disruption.